188 W nanosecond pulsed fiber amplifier at 1064 nm. (22nd June 2016) - Li, Zebiao; Guo, Chao; Li, Qi; Zhao, Pengfei; Li, Chengyu; Huang, Zhihua; Tang, Xuan; Lin, Honghuan; Xu, Shanhui; Yang, Zhongmin; Wang, Jianjun; Jing, Feng
Abstract: We report an all-fiber high power nanosecond pulsed laser at a center wavelength of 1064 nm. Optimizing the coiling diameter of the active fiber, 188 W average power is achieved at a repetition rate of 40 kHz. The pulse width is measured as 101 ns, while the peak power can be estimated to 46.5 kW.